A Case of Rhabdomyolysis Taking Senna - Özlem Tolu Kendir; Hayri Levent Yılmaz; Sevcan Bilen; Rıza Dinçer Yıldızdaş; Özden Özgür Horoz; Sinem Sarı Gökay; Gülsen Kendir (Galenos Yayinevi, 2019)
Rhabdomyolysis (RML) is a clinical condition that results in the release of the cellular content into the circulation due to musculoskeletal damage caused by various causes. For this reason, emergency departments should recognize RML and start treatment without any delay. In this study, we present a case of secondary RML in a 14-year-old patient followed up with the diagnosis of subacute sclerosing panencephalitis. Respiratory and circulatory support was provided in the emergency unit and alkalization was started. All medications used by the patient were cut off. Hemodiafiltration treatment was performed in our intensive care unit. It was learned that the patient have used the senna plant regularly for five years because of constipation. It has been reported in the literature that the senna plant has toxic effects on the brain, liver, kidney, heart and muscle, and also may cause renal tubular necrosis, centrilobular hepatic necrosis and muscle fiber necrosis. In this case report, we aimed to emphasize that the senna plant sold by herbalists and used frequently by people may cause secondary RML which may be a life-threatening condition.